Evaluation of heavy metals and their potential risk to human health from seafood in Escravos Estuary, Southern Nigeria - Abraham O. Ekperusi, Amaka Michael, Chidiogo H. Chukwurah, Naomi M. Sunday (My University, 2024)
In this study, we investigated the levels of heavy metals in sediment, shrimps, silver catfish and their potential bioaccumulation, trophic transfer and the associated risk to human health from the Escravos estuary in southern Nigeria. The values of heavy metals in shrimps and silver catfish were disproportionately higher than the allowable limits for seafood, with values in the gills and the rest of the fish higher than those of the muscle, liver and gonads. Furthermore, the increased BSAF for Cd, Cr and Cu in the study, underscore the uptake of metals from sediments into shellfish. High EDI and HR values from silver catfish for adults and children indicate im mediate health risks, with the values for children considerably high, emphasizing the urgent need for regulatory measures and continuous monitoring of seafood from the estuary to protect the health of coastal population within the subregion.
Keywords: Metal pollution Risk assessment Seafood safety Coastal monitoring One health Blue economy